2020
DOI: 10.9770/jesi.2020.7.4(24)
|View full text |Cite
|
Sign up to set email alerts
|

The effect of artificial intelligence on the sales graph in Indian market

Abstract: Artificial Intelligence (AI) has been the biggest revolution of the 21st century impacting every aspect of the business, sales being no different. The paper experiments the effect of marketing on 4500 customers using AI and humans. The outcomes of the research reveal the effectiveness of AI is the same as experienced salesmen and 2.7 times better than inexperienced salesmen is closing the sales calls. The sales graph experienced a dip by over 86.23% when it was revealed to the customer that the interface is wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Kollat and Willett (1967) contend that in-store stimuli remind the customers of their present or future needs. Impulse purchase involves the minimal expenditure of resources like time, physical and mental effort, and money (Ullal et al, 2020;Stern, 1962). A study by Abratt and Goodey (1990) showed customers spend more money than intended, which is against the views of Kollat and Willet that "there is a strong tendency for actual expenditure to approximate spending intentions".…”
Section: Literature Reviewmentioning
confidence: 96%
“…Kollat and Willett (1967) contend that in-store stimuli remind the customers of their present or future needs. Impulse purchase involves the minimal expenditure of resources like time, physical and mental effort, and money (Ullal et al, 2020;Stern, 1962). A study by Abratt and Goodey (1990) showed customers spend more money than intended, which is against the views of Kollat and Willet that "there is a strong tendency for actual expenditure to approximate spending intentions".…”
Section: Literature Reviewmentioning
confidence: 96%
“…Emotions play a major role in customers' decisions (Zablocki et al, 2019). Emotions are more in persuasive advertisements (Lau-Gesk & Meyers-Levy, 2009), and the feeling developed towards the advertisement is the feeling towards the brand (Orth & Holancova, 2003;Ullal et al, 2020). Advertisements are aimed at capturing customers' emotions and increasing sales (Kotler & Rath, 1984) and at branding products emotionally (Park et al, 2010).…”
Section: Literature Review and Hypothesis Formulationmentioning
confidence: 99%
“…Furthermore, the year of 2020 is marked by the discussion of the AI impact on the United Nations (UN) Sustainable Development Goals (SDGs). The fact that some countries are more open culturally and economically than others to the implementation of AI systems, creates new inequalities [54,55] widely discussed in literature. 2) the link between the nodes represents the co-occurrence between keywords (i.e., keywords that co-occur or occur together), (3) the thickness of the link signals the occurrence of co-occurrences between keywords (i.e., the number of times that the keywords co-occur or occur together), (4) the bigger the node, the greater the occurrence of the keyword, and (5) the thicker the link between nodes, the greater the occurrence of the co-occurrences between keywords.…”
Section: Co-occurrences Of Abstractmentioning
confidence: 99%